KULT-DICHTER VS. KULT DES DICHTERS: DAS PORTRÄT TARAS SCHEWTSCHENKOS IN „DIE VERHINDERTE REDE VON KIEW“ VON FRIEDRICH DÜRRENMATT - Voloshchuk, Ievgeniia (Porównania, 2018)
The paper focuses on the essay “My Stumbling Speech in Kyiv” by Friedrich Dürrenmatt which hitherto has been on the sidelines of Dürrenmatt studies. The literary portrait of a well-known Ukrainian poet Taras Shevchenko as a cultural “Other” and the self-projection of the essay’s author have been analyzed here in their interrelations with various cultural and political contexts.